In Vitro Development of Ovine Embryos Following Maturation Under Limited CO2 - ENDANG TRI MARGAWATI (Bogor Agricultural University, Indonesia, 2005)
An experiment was conducted to examine the influence of CO2 during in vitro oocyte maturation on the in vitro ovine embryo development. Three treatments of CO2 were subjected to the oocyte development. Those were 2h gasses prior to maturation in incubator (T1); without CO2 either prior to or over maturation (T2) and CO2 exposure both prior to and over 22h maturation (T3). A total of 324 oocytes were used. Putative zygotes were cultured for seven days and evaluated for their developmental stage. Presence of CO2 (T3) increased the proportion of oocytes reaching Metaphase II ( 66.50 + 3.5%; p